SISTEM INFORMASI PENJUALAN SEPATU BERBASIS WEB PADA TOKO SEPATU PREMIUM - Alisra, Muhammad Okka (CV SWA Anugerah, 2024)
Premium Shoe Shop is a business shop that sells women's and men's shoes. The Premium Shoe Shop is located in the Tanjung Raja area, Ogan Ilir Regency, South Sumatra. Premium Shoe Store opened or started a new start in December 2022. This shop sells men's Wamita shoes and various kinds of shoe brands and others besides. The Premium Shoe Shop is engaged in the buying and selling business, you can come to the shop or you can also buy online at the Premium Shoe Shop. Sales at the Premium Shoe store are slow and inefficient, both in terms of cost and time. An information system is needed that can facilitate the implementation of sales transactions and serve as a promotional event. So it is hoped that it can increase sales at the shop and compete with other shoe shops.